Educational articleOutpatient combined intracavitary and interstitial cervical brachytherapy: barriers and solutions to implementation of a successful programme – a single institutional experience - Tan, Poh Wee; Koh, Vicky Y.; Tang, Johann I. (Journal of Contemporary Brachytherapy, 2015)
Involvement of parametrial disease in locally advanced cervical patients poses a challenge for women undergoing brachytherapy. Current use of the Fletcher suit applicator may not adequately cover the high risk clinical target volume (HR CTV), especially in the parametrial region due to the physical qualities of brachytherapy from the inverse square law and the need to respect organs at risk (OAR) constraints, and leads to lower local control rates. Combined intracavitary and interstitial brachytherapy with the use of 1 or 2 interstitial needles allows adequate coverage of the HR CTV and the clinical evidence have demonstrated a correlation with better clinical results. This procedure is often resource intensive, requiring inpatient stay and magnetic resonance imaging (MRI) planning. In departments where such resources are limited, there is a poor uptake of interstitial brachytherapy. This article discusses the technique of combined intracavitary and interstitial brachytherapy in an outpatient setting, and explores the issues and barriers for implementation and suggestions to overcome such barriers.